Probing the adhesion interactions of graphene on silicon oxide by nanoindentation. (July 2016) - Suk, Ji Won; Na, Seung Ryul; Stromberg, Ryan J.; Stauffer, Douglas; Lee, Jinkee; Ruoff, Rodney S.; Liechti, Kenneth M.
Abstract: Although a variety of fundamental mechanical properties of graphene have been investigated, the nature of interactions between graphene and other materials is not yet fully understood. Here, we report on adhesive interactions between diamond indenters and monolayer, bilayer and trilayer graphene on silicon oxide as well as bare silicon oxide and graphite over relatively small spatial domains. Displacement-controlled nanoindentation with an ultralow noise force sensor allowed the complete adhesive responses to be observed without the usual instabilities associated with nanoindenters that operate in force control. It was found that the approach and withdrawal force profiles between diamond and graphene depended on the number of layers of graphene. The unloading response contained very characteristic features, which were attributed to separation between graphene and silicon oxide in subsequent stress analyses of the experiments. The numerical stress analyses accounted for the interactions between the probe and the graphene as well as between graphene and silicon oxide via traction–separation relations which included attractive and repulsive interactions. As a result, it was possible to extract the energy, strength and range of the interactions for all cases, thereby providing a much richer measure of the interactions than relying solely on force profiles.